US Hegemony and the Americas: Power and Economic Statecraft in International Relations - Híjar-Chiapa, Miguel (México y la Cuenca del Pacífico, 2020)
Santa-Cruz, Arturo. (2020). US Hegemony and the Americas: Power and Economic Statecraft in International Relations. Oxon: Routledge.